O impacto do padrão de moradia popular para acessibilidade no modo de vida dos moradores - Adriana Rodrigues Leao (2011)
The present research paper presents a descriptive and reflective analysis about the quality of usage patterns as based on accessibility for everyone in low-income affordable housing that are financed by the State of Minas Gerais, which include accessibility for all. The research is based on making a comparison between two housing type models that run by the State Company for Low income Housing COHAB-MG: Home environments that were specially designed to be wheelchair accessible and home environments for ordinary user profiles with no considerations of design requirements of ABNT 9050-2004. Intends to examine how the model specially designed for accessibility can change the lifestyle of families and can confirm to reduce the problem of quality residential use. The methodology included data collection of official information, observation sessions in field visits, interviews and data analysis. Results show that the lifestyle of the residents does not evidence efficiency of minimum accessible design set by COHAB-MG as evidenced by individual needs for place-making; the excessive number of people as residents, the number, shape and location of large furniture , among others. Therefore, the space designed to be accessible is inaccessible since the original design concept and users engaged in the process place-making.